2021
DOI: 10.3390/sym13020258
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Hydrogen-Bonded Cage Tetramers of Phosphonic Acid

Abstract: The self-association of phosphonic acids with general formula RP(O)(OH)2 in solution state remains largely unexplored. The general understanding is that such molecules form multiple intermolecular hydrogen bonds, but the stoichiometry of self-associates and the bonding motifs are unclear. In this work, we report the results of the study of self-association of tert-butylphosphonic acid using low temperature liquid-state 1H and 31P NMR spectroscopy (100 K; CDF3/CDF2Cl) and density functional theory (DFT) calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Due to the more flexible geometry and non-planarity of a POOH group compared to carboxylic acids, phosphinic and phosphonic acids are also able to form various cyclic associates in a polar aprotic solution – trimers and tetramers with hydrogen bonds. 15,16…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the more flexible geometry and non-planarity of a POOH group compared to carboxylic acids, phosphinic and phosphonic acids are also able to form various cyclic associates in a polar aprotic solution – trimers and tetramers with hydrogen bonds. 15,16…”
Section: Introductionmentioning
confidence: 99%
“…8,11 Another example of a compound with the XOOH group and ability to participate in hydrogen bonding as the hydrogen bond donor and hydrogen bond acceptor is phosphinic acids R 1 R 2 POOH, which have been actively researched during the past decades. [15][16][17][18][19][20][21] It was found that similar hydrogen-bonded selfassociates of phosphinic acids are stronger than that of carboxylic acids. For example, the dimerization enthalpy of the dimethylphosphinic acid Me 2 POOH is about 23-24 kcal mol À1 19,22 and it is almost twice the enthalpy measured for acetic acid dimers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, many useful methods focused on structure and reactivity analysis have been described. The quantum theory of atoms in molecules (QTAIM) analysis gives clear information about covalent and non-covalent interactions [28][29][30]. Previously, several closo-borate anions have been calculated by QTAIM analysis [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate theoretical calculations make it possible to fully understand the relationship between different parameters of the system under study and to facilitate the search for optimal correlations [27][28][29][30][31]. Such calculations are often the only method for studying weak non-covalent interactions [32][33][34][35][36] or molecular systems with competing interactions [37][38][39][40][41][42]. However, often these calculations require a very careful selection of the systems to be examined.…”
Section: Introductionmentioning
confidence: 99%